HUBUNGAN AKSES SANITASI DASAR DAN KUALITAS AIR MINUM DENGAN KEJADIAN DIARE PADA BALITA DI PUSKESMAS AMPANA BARAT - Hasanah Hasanah; Siti Aynur Rofiq; Nurdin Nurdin; Pitriani Pitriani (Jurnal Kesehatan Tambusai, 2023)
Diarrhea is still a health problem in Indonesia, this is due to the high morbidity of diarrhea which can cause death, especially in children under five. Low access to basic sanitation, such as the availability of adequate clean water and minimal use of healthy latrines, unsanitary drinking water may lead a toddler experience diarrhea. This research is quantitative with cross sectional approach, with 169 people as a population. 63. Whereas the sample of drinking water carried out according to SNI 06-4158-1996. Bacterial analysis of samples was carried out using the MPN method in the laboratory of the Ampana District Health Office. The results showed that the presence of Escherichia coli in drinking water was associated with the incidence of diarrhea in toddlers (p=0.000). Of the 63 samples of drinking water examined, there were 35 samples not meet the bacteriological requirements of drinking water. all drinking water samples that tested positive for bacteria came from refill drinking water depots, while samples of boiled drinking water did not contain E-coli bacteria contamination. Meanwhile, the availability of clean water and latrines were not related to the incidence of diarrhea in toddlers (p=1,000). all respondents have access to adequate basic sanitation facilities, they have sufficient clean water and already have a latrine. Based on this data it was concluded that the presence of bacteria in the refill drinking water consumed by the community in the working area of the West Ampana Health Center is related to the incidence of diarrhea in toddlers. The local government, in this case the West Ampana Health Center, needs to tighten monitoring of the quality of drinking water through regular inspections of refill drinking water depots, so that the quality of refill drinking water circulating in the community is guaranteed.